Bridging the Gap Between Mammal and Insect Ears – A Comparative and Evolutionary View of Sound-Reception - Warren, Ben; Nowotny, Manuela (Frontiers in Ecology and Evolution, 2021)
Insects must wonder why mammals have ears only in their head and why they evolved only one common principle of ear design – the cochlea. Ears independently evolved at least 19 times in different insect groups and therefore can be found in completely different body parts. The morphologies and functional characteristics of insect ears are as wildly diverse as the ecological niches they exploit. In both, insects and mammals, hearing organs are constrained by the same biophysical principles and their respective molecular processes for mechanotransduction are thought to share a common evolutionary origin. Due to this, comparative knowledge of hearing across animal phyla provides crucial insight into fundamental processes of auditory transduction, especially at the biomechanical and molecular level. This review will start by comparing the evolution of hearing between insects and mammals to bring together results from both auditory research communities. The discussion of current findings about sound reception will help to bridge the gap between both research fields.